Checkpoint inhibitors as dual immunotherapy in advanced non-small cell lung cancer: a meta-analysis - Alifu, Muyesar; Tao, Min; Chen, Xiao; Chen, Jie; Tang, Kejing; Tang, Yubo (Frontiers in Oncology, 2023)
Introduction Recent clinical trials have confirmed that anti-programmed cell death-1/ligand 1 (anti-PD-1/L1) combined with either anti-cytotoxic T-lymphocyte-associated protein 4 (anti-CTLA-4) or anti-T-cell immunoreceptor with Ig and ITIM domains (TIGIT) antibodies (dual immunotherapy) produced significant benefits as first-line therapies for patients with advanced non-small cell lung cancer (NSCLC). However, it also increased the incidence of adverse reactions, which cannot be ignored. Our study aims to explore the efficacy and safety of dual immunotherapies in advanced NSCLC. Methods This meta-analysis ultimately included nine first-line randomized controlled trials collected from PubMed, EMBASE, and Cochrane Central Register of Controlled Trials databases until 13 August 2022. Efficacy was measured as the hazard ratio (HR) and 95% confidence interval (CI) for progression-free survival (PFS), overall survival (OS), and risk ratio (RR) for the objective response rates (ORRs). Treatment safety was assessed by RR of any grade of treatment-related adverse events (TRAEs) and grade ≥ 3 TRAEs. Results Our results demonstrated that, compared to chemotherapy, dual immunotherapy shows durable benefits in OS (HR = 0.76, 95% CI: 0.69–0.82) and PFS (HR = 0.75, 95% CI: 0.67–0.83) across all levels of PD-L1 expression. Subgroup analysis also presented that dual immunotherapy resulted in improved long-term survival compared with chemotherapy in patients with a high tumor mutational burden (TMB) (OS: HR = 0.76, p = 0.0009; PFS: HR = 0.72, p < 0.0001) and squamous cell histology (OS: HR = 0.64, p < 0.00001; PFS: HR = 0.66, p < 0.001). However, compared with immune checkpoint inhibitor (ICI) monotherapy, dual immunotherapy shows some advantages in terms of OS and ORR and only improved PFS (HR = 0.77, p = 0.005) in PD-L1 < 25%. With regard to safety, there was no significant difference in any grade TRAEs (p = 0.05) and grade ≥ 3 TRAEs (p = 0.31) between the dual immunotherapy and chemotherapy groups. However, compared with ICI monotherapy, dual immunotherapy significantly increased the incidence of any grade TRAEs (p = 0.03) and grade ≥ 3 TRAEs (p < 0.0001). Conclusions As for the efficacy and safety outcome, compared with standard chemotherapy, dual immunotherapy remains an effective first-line therapy for patients with advanced NSCLC, especially for patients with high TMB levels and squamous cell histology. Furthermore, compared to single-agent immunotherapy, dual immunotherapy is only considered for use in patients with low PD-L1 expression in order to reduce the emergence of resistance to immunotherapy. Systematic Review Registation https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42022336614.